The effect of short-term and long-term coronavirus quarantine on physical performance and injury incidence in high-level soccer - Guerrero-Calderón, B. (Soccer & Society, 2020)
In 2020, the world is suffering an unprecedented pandemic (coronavirus or COVID-19) that it is eliciting devastating consequences. This article has gathered the opinions of international soccer experts about the short-term and long-term effects of coronavirus quarantine on physical performance and injury incidence in high-level soccer players, by means of open-ended questions encouraging the expression of unrestricted opinions. In this way, the text aims to provide the reader with a compilation and comparison of knowledge from a practical perspective in order to understand how the coronavirus quarantine may affect the high-level players` physical performance from the extensive experience and broad career of conditioning area professionals in top-level soccer teams around the world together with the knowledge provided by research. Fulltext in ResearchGate